Corrigendum: Interleukin-13 as a potential biomarker in the management of pediatric asthma – a longitudinal study - Raju, Prasanna; Sundar, Subash; Suresh, Preethi; Vajravelu, Leela Kakithakara; Aravindhan, Vivekanandhan (European Journal of Clinical and Experimental Medicine, 2025)
<p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">A Corrigendum on <p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Interleukin-13 as a potential biomarker in the management of pediatric asthma – a longitudinal study by Raju P, Sundar S, Suresh P, Vajravelu LK, Aravindhan V. Eur J Clin Exp Med. 2025;23(1):15–20. doi: 10.15584/ ejcem.2025.1.3.